2016
DOI: 10.1190/int-2015-0225.1
|View full text |Cite
|
Sign up to set email alerts
|

Reflection imaging of aseismic zones of the Nazca slab by global-phase seismic interferometry

Abstract: Obtaining detailed images of aseismic parts of subducting slabs remains a large challenge for understanding slab dynamics. Hypocenter mapping cannot be used for the purpose due to the absence of seismicity, whereas the use of receiver functions might be compromised by the presence of melt. Global tomography can be used to identify the presence of the slab, but it does not reveal the structure in detail. We have determined how detailed images can be obtained using global-phase seismic interferometry. The method… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0
5

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 46 publications
1
11
0
5
Order By: Relevance
“…6). Nishitsuji et al (2016) confirmed such Moho structures by global-phase seismic interferometry (the blue dotted lines in Fig. 6).…”
Section: Figuresupporting
confidence: 65%
See 1 more Smart Citation
“…6). Nishitsuji et al (2016) confirmed such Moho structures by global-phase seismic interferometry (the blue dotted lines in Fig. 6).…”
Section: Figuresupporting
confidence: 65%
“…Based on the obtained MDD image, we think that LEPC SI, together with resistivity investigations, might be useful for enhanced geothermal-systems characterization. Gilbert et al (2006) and Nishitsuji et al (2016). The green line indicates a major deep basement thrust fault by the exploration well (LPis x-1).…”
Section: Figurementioning
confidence: 99%
“…Compared to earlier studies (e.g. Ruigrok & Wapenaar 2012;Nishitsuji et al 2016) this ray parameter limit is slightly higher, allowing to include additional teleseismic events, namely P-phase events originating at a distance of at least 80 • . The long lifespan of these stations implies that a large number of earthquakes have been recorded; over 2000 earthquakes with a magnitude >6.4 occurred from the first recording in 2008 until April 2018.…”
Section: Theorymentioning
confidence: 95%
“…La ISmA es una herramienta robusta, de manera tal que ha sido aplicada con diferentes tipos de datos, en diferentesáreas y a distintas escalas; por ejemplo, esta técnica ha sido aplicada a fases globales y telesísmicas (aquellas que se propagan por el núcleo y el manto, respectivamente, antes de arribar a la estación) para obtener imágenes del subsuelo cortical a escala regional (Ruigrok and Wapenaar, 2012;Nishitsuji et al, 2016), a ondas P de microsismos para caracterizar el subsuelo volcánico somero (Kim et al, 2017), y a registros de ruido sísmico ambiental (Draganov et al, 2007b;Gorbatov et al, 2013;Boullenger et al, 2014;Oren and Nowack, 2017).…”
Section: Iv3 Interferometría Sísmica Mediante Autocorrelacionesunclassified
“…Si bien las aplicaciones de ISmA a fases globales (Nishitsuji et al, 2016), a sismos regionales y telesismos (Casas et al), y a sismos locales (Casas et al, 2019) presentan la misma esencia, es decir, la utilización del teorema general de reciprocidad por correlación (representada por la Ecuación IV.5); el flujo de trabajo posee diferencias notables, relevantes a las condiciones de las bases de datos utilizadas. A continuación, se detalla el correspondiente a la aplicación a datos de sismos regionales y telesismos.…”
Section: V13 Aplicación a Sismos Regionales Y Telesismosunclassified